Impact of Media on Political Awareness in the 2023 General Election in Nigeria: A Study of Some Selected Radio Stations in Gombe State - Babayo Sule; Balla Lummo Kachalla (Pen of Social Science, 2026)
Media, both mainstream and social, are now the hallmark of socioeconomic and political life in contemporary societies. It serves as a viable option for reaching a large audience in a limited time. Nigeria is a populous country with a widespread geographical terrain that makes physical contact, especially by politicians during campaigns, a herculean task. However, the advent of the media eased the process of campaigning, political communication, and awareness creation among the electorates in the Fourth Republic. One area where the media plays a significant role in political communication is Gombe State during the 2023 General Election. This study examines the impact of the media on political awareness in the 2023 General Election in Gombe State using some selected radio stations. The study adopted a mixed-methods research design. Data were obtained from fieldwork and documented sources. Questionnaires were administered in selected areas using purposive random sampling, while key informant interviews were conducted with relevant stakeholders in addition to FGD. The collected data were discussed and analysed using non-automated SPSS. The study reports that the media played an influential role in shaping public opinion, perception, and voting choice and pattern in Gombe State. This remarkable feat was achieved because local languages, particularly Hausa, were being used as the lingua franca. It is recommended that civic education programmes be sponsored by NGOs and other institutions that support democracy to create conscience and empower the locals to follow policies and be involved in the policy-making process, as well as to continue to participate in elections in the future.